1995
DOI: 10.4315/0362-028x-58.8.829
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Survival of Salmonella montevideo on Tomatoes and Disinfection with Chlorinated Water

Abstract: The survival on tomato fruits (Lycopersicum esculentum) of a rifampicin-resistant strain of Salmonella montevideo (Centers for Disease Control and Prevention [CDC] isolate G4639), the alleged source of the 1993 multistate outbreak of salmonellosis, was affected by inoculum dose and inoculation site (unbroken surface or wounds and stem scars), as well as by the medium (distilled water, Butterfield's buffer, or trypticase soy broth [TSB]) used to deliver the bacterium, This bacterium inoculated at 4 log10 CFU (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(94 citation statements)
references
References 4 publications
4
88
0
2
Order By: Relevance
“…Our previous study [24] showed that minimum initial inoculum size for the S. typhimurium growth on the tomato surface was determined to be 3 log CFU/tomato surface with diluted nutrients. These findings agreed with Wei et al 's [31] study (1995) in that S. Montevideo could grow with the help of nutrients (for example, in puncture wounds). Without any nutrient sources, the bacteria could only survive for several days on tomato surfaces at 20 and 25°C.…”
Section: Observation and Enumeration Of S Typhimurium Directly Grownsupporting
confidence: 82%
“…Our previous study [24] showed that minimum initial inoculum size for the S. typhimurium growth on the tomato surface was determined to be 3 log CFU/tomato surface with diluted nutrients. These findings agreed with Wei et al 's [31] study (1995) in that S. Montevideo could grow with the help of nutrients (for example, in puncture wounds). Without any nutrient sources, the bacteria could only survive for several days on tomato surfaces at 20 and 25°C.…”
Section: Observation and Enumeration Of S Typhimurium Directly Grownsupporting
confidence: 82%
“…There is a controversy about the formation of carcinogenic chlorinated compounds in water (chloramines and trihalomethanes), calling into question the use of chlorine (Wei et al, 1999). The current concern associated with chlorine outlines the need for research on other treatments suitable for use on fresh-cut products.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine solutions have been widely used to sanitise fresh-cut fruits and vegetables in the industry. However, the possible formation of carcinogenic chlorinated compounds in water has called into question the use of chlorine in food processing plants (Dychdala, 1991;Page, Harris, & Epstein, 1976;Wei et al, 1999). Moreover, the antimicrobial effectiveness of cold chlorinated water is limited due to hydrophobic plant surfaces that are believed to limit contact between chlorine solutions and microbial contaminants (Adams, 1991;Beuchat, 1992).…”
Section: Introductionmentioning
confidence: 99%